Rancang Bangun Alat Pengering Kerupuk Kulit Dengan Pemanas Heater Menggunakan Fuzzy Logic Berbasis Mikrokontroler - Ramadhan, Muh. Riski; Darmawan, Budi; Suksmadana, I Made Budi (TIN: Terapan Informatika Nusantara, 2024)
Livestock leather is a food ingredient that can be processed using various types of preparations, one of which is into leather crackers. The processing of leather crackers is done by drying which reduces the water content to the required limit. The processing process requires a long process with the help of sunlight for drying which takes 1-2 days. This research aims to design and develop a skin cracker drying system by utilizing a control-based method fuzzy logic to speed up the drying process of skin crackers. This system consists of a temperature sensor, a weight sensor. Testing of this system has been carried out using several pieces of skin as samples. The research results show that the control method is based on fuzzy logic can stabilize the temperature to the desired for the drying process. Application of heating control methods based on fuzzy logic The skin cracker drying machine is designed at a set point temperature of 50°C so that it can help reduce the weight of the crackers linearly so that the skin crackers are wet weighing 3kg to 973 grams which takes 7 hours.